Cystic Hygroma of Wrist - Wani, I; Bhat, AR; Amin, A; Wani, S; Malik, R (Journal of Nepal Paediatric Society, 2012)
Cystic hygroma is the rare congenital lesion. This is a cystic variety of lymphangioma. Cystic hygroma arising outside of the cervicofacial, thoracic, and abdominal areas are extremely rare. Wrist is a very rare site for occurrence of cystic hygroma. Presentation depends on site of location of cystic hygroma. A case of cystic hygroma of wrist in a child is reported. This child presented with painless swelling of left wrist. Excision of cyst was done. This is first case report of literature reporting occurrence of cystic hygroma on wrist. J Nepal Paediatr Soc 2012;32(2):166-168 doi: http://dx.doi.org/10.3126/jnps.v32i2.5465